Analysis Stock Price Comparison with Price To Book Value (PBV) Method as the Basis for Investment Decisions At Starup Indonesia Company - Nopiana, Puspita Rama; novita, wellia (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The research is motivated by the antuasias of the Indonesian people who want to invest today, especially in the era of digitalization, it is so easy to be able to make stock buying and selling transactions. Moreover, it is supported by the rise of starup issuers that have been listed on the Indonesia Stock Exchange. The purpose of this study provides an overview of fundamental stock analysis using the 2021 Price To Book Value (PBV) method in companies with the starup logo in Indonesia as the basis for investment decisions for investors or potential investors. This research method is quantitative descriptive, where there are 9 starup companies that have entered the capital market from 2017-2021. The results of this study show that of all starup issuers there are four issuers, namely PT Yelooo Integra Datanet Tbk., PT Yelooo Integra Datanet Tbk., PT Yelooo Integra Datanet Tbk., and PT Bukalapak.com Tbk. which are still in low stock prices. Meanwhile, the other 5 issuers stated that the stock price was quite expensive. Furthermore, all issuers are eligible as an option to invest, where only the issuer of PT Yelooo Integra Datanet Tbk. has an undervalued position, where the market price is lower than its book value. The rest are in an overvalued position, where the market price is higher than the book value. PBV analysis is one of the fundamental analyses that can be used as a basis for investment considerations, it is expected for investors or potential investors and other researchers to be able to use other analyses such as Price Earning Ratio (PER), Return On Equity (ROE), Devident Payout Ratio (DPR) and others as a basis for making investment decisions, especially in the long term